Diversity assessment of winged bean [Psophocarpus tetragonolobus (L.) DC.] accessions from IITA Genebank - Shonde, T.E.; Adebayo, M.A.; Bhadmus, A.; Adejumobi, I.I.; Oyatomi, O.; Faloye, B.; Abberton, M. (MDPI, 2023)
The capability of winged bean to support food and nutrition security in sub-Saharan Africa is recurrently being affected by several constraints, which include a lack of genetic improvement. The dearth of adequate information on the level of available genetic diversity in winged bean germplasm has been a major setback in planning appropriate improvement programs. Fifteen winged bean accessions were assessed for genetic diversity using 10 quantitative traits and 10 simple sequence repeat (SSR) markers. The accessions were laid out in RCBD with three replicates for two growing seasons. Leaf samples were obtained from 10 plants representing each accession for SSR marker genotyping. The accessions exhibited significant (p < 0.05) differences for measured traits. Broad-sense heritability estimates varied from 10.31% for days to first plant maturity to 72.67% for pod weight. Pod weight had a positive and significant correlations with pod length (0.53, p < 0.05), pod width (0.70, p < 0.01), and number of seeds per pod (0.64, p < 0.01). However, the number of seeds per pod was negatively correlated with days to maturity (−0.71, p < 0.01). Number of seeds per pod was positively predicted by pod weight, seed thickness, and days to maturity. Cluster analysis delineated the accessions into two distinct groups. Average number of alleles of 4.2, gene diversity of 0.25, and polymorphic information content of 0.22 were recorded. Analysis of molecular variance revealed intra-accession variation of 95% as compared to inter-accession variation of 5%. Two primary genetic groups were identified and only three accessions, namely TPt-6, TPt-126, and TPt-48, showed genetic purity. The results of this study provide the basis for exploiting the existing diversity for winged bean improvement.